Spatial Evaluation of Urban Zoning in Moncongloe, Mamminasata New City, Indonesia - Aslam Jumain; Syafri; S. Kamran Aksa (Universitas Katolik Indonesia Atma Jaya, 2025)
Urban zoning plays a crucial role in ensuring sustainable spatial development, especially in emerging planned cities. This study evaluates the spatial structure and regulatory compliance of land-use zoning in Moncongloe, a strategic development unit of the Mamminasata New City in South Sulawesi, Indonesia. Using a descriptive-evaluative spatial approach, the analysis examines the alignment of the Detailed Spatial Plan (RDTR) with national planning standards, particularly focusing on land-use distribution, urban green space provision, and zoning balance. Results show a significant mismatch between planned land-use and regulatory requirements, with green open space accounting for only 0.35% of the total area far below the 30% minimum threshold mandated by ATR/BPN Regulation No. 14/2022. Residential zones dominate over 61% of the planning area, while protected, agricultural, and public service zones remain underrepresented. The study recommends spatial reallocation strategies, formal recognition of agro-ecological zones such as minapadi, and GIS-based zoning audits to enhance compliance and ecological resilience. These findings highlight the need for more integrative, regulation-aligned urban planning in Indonesia’s new city developments.